Driveline Infection Risk with Utilization of a Temporary External Anchoring Suture After Implantation of a Left Ventricular Assist Device. Issue 3 (May 2016) - Fudim, Marat; Brown, Christopher L.; Davis, Mary E.; Djunaidi, Monica; Danter, Matthew R.; Harrell, Frank E.; Stulak, John M.; Haglund, Nicholas A.; Maltais, Simon
Abstract : Driveline infections (DLI) are a cause of morbidity after continuous-flow left ventricular assist device (CF-LVAD) implantation. Because driveline trauma contributes to DLI, we assessed whether intraoperative placement of a temporary external anchoring suture (EAS) influenced DLI rate. We analyzed 161 consecutive patients with CF-LVAD (HMII 82; HW 79) implantation. Two groups were defined: placement of EAS (n = 85) or No EAS (n = 76). For NO EAS patients, the driveline was permanently anchored internally to the rectus fascia. Cox proportional analysis was performed to assess the effect of EAS on time to first confirmed DLI. Baseline characteristics were comparable between groups (all p = 0.3). Mean follow-up time was 0.93 years. A total of 18 (11.1%) patients developed confirmed culture positive DLI, with "first infection" rate of 0.13 events/year. Mean time to confirmed DLI was 0.69 years. Driveline infection was less likely (hazard ratio [HR] = 0.28, 0.95 confidence interval [CI] = 0.06–1.25, p = 0.056) to occur in NO EAS (2/18) then in EAS (16/18). Confirmed DLI was comparable between device types ( p = 0.3). Multivariable regression adjusted for age, BMI, blood product use, device type, and diabetes showed equivocal effect of EAS (HR = 0.33, 0.95 CI = 0.07–1.54, p = 0.12). Patients with a temporary EAS may have an increased risk of confirmed DLI after device implantation.